The Interaction of TPH1 A779C Polymorphism and Maternal Authoritarianism on Creative Potential - Zhang, Jinghuan; Han, Xiao; Si, Si; Zhang, Shun (Frontiers in Psychology, 2018)
Exploring the possible mechanisms through which gene may interact with environment to influence creativity has been one of the leading issues in creativity research. In a sample of four hundred and twenty-one Chinese undergraduate students, the present study investigated for the first time the interaction of TPH1 A779C polymorphism and maternal parenting styles on creative potential. The results showed that there was a significant interaction of TPH1 A779C polymorphism and maternal authoritarianism on creative potential. Moreover, the analysis of regions of significance (Ros) provided supporting evidences for both the diathesis-stress model (flexibility) and the differential susceptibility model (originality). These findings extend our understanding concerning the mechanisms by which gene and environment may act in coordination to contribute to creativity.